2021
DOI: 10.1002/glia.24088
|View full text |Cite|
|
Sign up to set email alerts
|

N‐3 PUFA deficiency disrupts oligodendrocyte maturation and myelin integrity during brain development

Abstract: Westernization of dietary habits has led to a progressive reduction in dietary intake of n‐3 polyunsaturated fatty acids (n‐3 PUFAs). Low maternal intake of n‐3 PUFAs has been linked to neurodevelopmental disorders, conditions in which myelination processes are abnormal, leading to defects in brain functional connectivity. Only little is known about the role of n‐3 PUFAs in oligodendrocyte physiology and white matter development. Here, we show that lifelong n‐3 PUFA deficiency disrupts oligodendrocytes maturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 119 publications
0
21
0
Order By: Relevance
“…We chose the latter based on the previous studies on myelin/microglia interactions during development (Hagemeyer et al, 2017;Kaur et al, 2017;Lee et al, 2019;Nemes-Baran et al, 2020;Traiffort et al, 2020). This is also in this area that we observed an alteration of myelination in mice deficient in n-3 PUFA in a former study (Leyrolle et al, 2021b). We focused on one part of the corpus callosum, the body that unites the motor, somatosensory and parietal regions (Wahl et al, 2007;Park et al, 2008;Putnam et al, 2010;Ku and Torii, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We chose the latter based on the previous studies on myelin/microglia interactions during development (Hagemeyer et al, 2017;Kaur et al, 2017;Lee et al, 2019;Nemes-Baran et al, 2020;Traiffort et al, 2020). This is also in this area that we observed an alteration of myelination in mice deficient in n-3 PUFA in a former study (Leyrolle et al, 2021b). We focused on one part of the corpus callosum, the body that unites the motor, somatosensory and parietal regions (Wahl et al, 2007;Park et al, 2008;Putnam et al, 2010;Ku and Torii, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this assumption, Kalafatakis and Karagogeos, 2021 have shown that the time course of microglial migration to the white matter correlates with the onset of OPCs generation in this structure. Interestingly, we previously demonstrated that maternal n-3 PUFA deficiency leads to hypomyelination of the corpus callosum at P21 and in the adult offspring, and to a significant decrease in the number of mature oligodendrocytes in the corpus callosum of juveniles, associated with long-term deficits in brain structures synchronization ( Leyrolle et al, 2021b ). Hence, while the total number of microglia was similar between both dietary groups at P15, the absence of a peak at P10 in n-3 deficient mice may have significant functional impacts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations